Applicant Attractiveness as a Perceived Job-Relevant Variable in Selection of Management Trainees - Beehr, Terry A.; Gilmore, Davìd C. (Academy of Management Journal, 1982)
This experiment manipulated the attractiveness of male applicants and the perceived relevance of attractiveness for managerial job performance in a two-by-two analysis of variance design. An interaction was predicted and found for the effects of the manipulation on hiring decisions and on job-specific attributions of ability.